2010
DOI: 10.1186/ar3119
|View full text |Cite
|
Sign up to set email alerts
|

A multiparameter approach to monitor disease activity in collagen-induced arthritis

Abstract: IntroductionDisease severity in collagen-induced arthritis (CIA) is commonly assessed by clinical scoring of paw swelling and histological examination of joints. Although this is an accurate approach, it is also labour-intensive and the application of less invasive and less time-consuming methods is of great interest. However, it is still unclear which of these methods represents the most discriminating measure of disease activity.MethodsWe undertook a comparative analysis in which different measurements of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 20 publications
(15 reference statements)
1
31
0
Order By: Relevance
“…MicroCT has become an important tool for the analysis of bone morphology and has previously been used in the CIA murine model (20). MicroCT analysis of the long bones from ox40l −/− mice revealed basal bone turnover defects (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MicroCT has become an important tool for the analysis of bone morphology and has previously been used in the CIA murine model (20). MicroCT analysis of the long bones from ox40l −/− mice revealed basal bone turnover defects (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2B). It has been reported that serum matrix metalloproteinase (MMP)-3 is a good indicator in the inflammatory aspect and cartilage damage of CIA (29). Serum levels of MMP-3 are elevated in RA, providing a useful marker of synovial inflammatory activity (30).…”
Section: Resultsmentioning
confidence: 99%
“…Micro-CT has been reported frequently for imaging and assessing ex vivo the effect of different types of arthritis on the bone structure (Buttgereit et al, 2009;Herrak et al, 2004), surface roughness (Seeuws et al, 2010) and density (Healy et al, 2006). Although this technique allows investigation of the effect of arthritis on the underlying bone, nothing can be concluded concerning cartilage structure and functionality.…”
Section: Discussionmentioning
confidence: 99%